Examining Cervical Cancer Awareness and Screening among Postpartum Women in a Nigerian Tertiary Hospital: Perspectives from Sub-Saharan Africa - Onyekachi Sunday Ohaeri; Peter Waripamo Oweisi; Azubuike Ikechukwu; Musa Stephen; Peter Waibode Alabrah; Adesina Adedotun Daniel (New Advances in Medicine and Medical Science Vol. 1, 2023)
This chapter aims to determine the awareness of and identify the sources of information on cervical cancer and screening uptake among post-partum women receiving care at a tertiary hospital in Bayelsa State, Nigeria, between June and October 2018. Risk factors for cervical cancer include early coitarche, high parity, multiple sexual partners, sexually transmitted infections, especially with oncogenic strains of human papillomavirus (HPV), and smoking. A total of 104 researcher-developed questionnaires were employed to collect data in this cross-sectional descriptive study. The same was researcher-administered to and retrieved from the respondents (52 HIV-positive and 52 HIV-negative), with data on sociodemographic characteristics, awareness of cervical cancer, screening programmes and methods, sources of information, factors related to cervical cancer, and uptake of cervical screening services were collected. The study participants were mostly young women, with a mean age of 31.12 + 4.46 and the majority (94.1%) had basic education. Nearly all participants (97.1%) were married, and most (98.0%) lived in monogamous family settings. 62.7% of the women had given birth to more than one child. Only 39.2% of participants have heard about cervical cancer, 17.3% have heard about cervical cancer screening, and only 1% have utilized (taken part in) a screening service. The main sources of information were health workers (47.5%) and print and mass media (47.5%). Identified risk factors included having more than one sexual partner (80.4%), multiparity (62.7%), and hormonal contraceptive use (37.3%). Despite being a preventable disease, there was little awareness of cervical cancer, screening, and almost no use of screening services in the study population. The findings indicate the importance of developing and implementing effective communication and service delivery methods to boost the use of cervical screening services in this community.